99mTc-MDP SPECT/CT Demonstrating Extraosseous Periarticular Amyloid Deposits in Primary Systemic Amyloidosis Associated With Multiple Myeloma. (February 2015) - Agarwal, Krishan Kant; Karunanithi, Sellam; Roy, Shambo Guha; Bal, Chandrasekhar; Kumar, Rakesh
<x xml:space="preserve">Abstract</x> Abstract Amyloidosis is a rare disorder characterized by variable extracellular accumulation of a complex substance consisting of proteinaceous fibrils (amyloid fibrils) and nonfibrillar glycoprotein or amyloid P component. We present a case of a primary systemic amyloidosis associated with multiple myeloma in a 48-year-old woman whose 99mTc-MDP SPECT/CT study revealed extraosseous periarticular uptake in amyloid deposits with no abnormal focal tracer uptake in the bone.